Pengaruh Kualitas Layanan dan Kualitas Produk Terhadap Kepuasan Nasabah Bank: (The Effect of Service Quality and Product Quality on Bank Customer Satisfaction) - Meli Andriyani; Riski Ardianto (LPPM Universitas Pelita Bangsa, 2020)
The bank as a service company places great importance on satisfaction through services and products. The purpose of this study was to determine the effect of service quality and product quality on customer satisfaction. The research was conducted by distributing questionnaires to 100 respondents, namely bank customers who live and have bank accounts in the Cibubur area. The research data were analyzed using multiple linear regression analysis. The study found that service quality did not affect customer satisfaction, while product quality had a positive effect on customer satisfaction.